Pediatricians 64 - Alexander S. Sozinov (Union of pediatricians of Russia, 2021)
Article is based on performance of the Rector of the Kazan State Medical University at the VIII Conference «Pediatrics and Pediatric Surgery in the Volga Federal District» September 20, 2011, devoted to the 70th anniversary of the famous Russian pediatricians - academician A.A. Baranov, professors V.Yu. Albitsky, A.V. Kuznetsova, S.V. Maltsev, O.I. Pikuza, who graduated Department of Pediatrics KSMA in 1964. Presents data on scientific creativity and contribution of anniversaries in pediatric science, to the protection of the health of the child population of Tatarstan and Russia.